A Study on the Competence Characteristics of Psychological Hotline Counselors During the Outbreak of COVID-19 - You, Linyu; Jia, Xiaoming; Ding, Yaping; An, Qin; Li, Bo (Frontiers in Psychology, 2021)
Introduction: After the outbreak of COVID-19, psychological hotlines functioned as a main channel of psychological assistance and required a large number of professionals to provide services. These hotlines mostly offer a single-use service with short session times and allow callers to retain anonymity. They functioned as a psychological counseling service for stress experienced in the COVID-19 public health emergency. Hotline psychological counselors must meet special competency requirements. The selection and evaluation tools for recruiting hotline counselors need to be developed. Materials and Methods: The initial scale of competence for psychological hotline counselors was formed by expert evaluation based on theoretical constructs and by using the Delphi method. A link to the questionnaire was sent to a WeChat group of counselors from 36 major psychological hotlines in China in two stages. The questionnaire consisted of questions to elicit basic demographic information and the initial competence scale. In the first phase, 343 valid samples were used to perform exploratory factor analysis. In the second phase, 334 valid samples were used to perform confirmatory factor analysis. The status of the competence of psychological hotline counselors was also analyzed. Results: The factor structure of the Psychological Hotline Counselor Competence Scale was verified and defined in terms of skills, attitude, and knowledge. The results of exploratory factor analysis and confirmatory factor analysis showed that the scale has good reliability and validity (χ²/df=1.758, GFI=0.86, RMSEA=0.05, CFI=0.96, NFI=0.91, NNFI=0.95). The McDonald’s omega for each factor was calculated (ωF1=0.927, 95%CI [0.914, 0.940]; ωF2= 0.958, 95%CI [0.951, 0.965]; ωF3= 0.954, 95%CI [0.945, 0.961]). Meanwhile, it was found that the psychological hotline counselors’ self-assessed competence had a high average score (n=334). Conclusion: The Competence Scale for Psychological Hotline Counselors for Major Public Emergencies developed in this study has good reliability and validity, and can be a reliable tool for organizing psychological assistance and screening hotline psychological counselors during public emergencies in the future.